PEMBUATAN BERAS TIRUAN DARI PATI SAGU HMT (HEAT MOISTURE TREATMENT) DENGAN PENAMBAHAN TEPUNG KACANG HIJAU (Vigna radiata) - Shanti Fitriani; Rahmayuni '; Indra Eka Putra (Universitas Riau, 2011)
Natural sago starch in general still have weaknesses that have a high gelatinizationproperties. At the time of ripening of natural sago starch had gelatinization so sticky duringcooking. HMT treatment (Heat Moisture Treatment) aims to reduce the level of sago starchgelatinization during cooking, so it is not sticky when cooked. Green beans are rich in proteinand â-carotene was added to support the value of artificial nutrition in rice. This study aims todetermine the value of some quality parameters of artificial rice of HMT sago starch with theaddition of green beans flour. Research experiments were conducted using CompletelyRandomized Design (CRD). The measuring parameters are: rice moisture content, ash content,starch content, amylose content and protein content, also organoleptic assessment include thecolor, flavor, aroma, texture and overall acceptance. Result showed there is significant effect onash content, starch content, amylase content, protein content and organoleptic assessment oncolor. But there is no significant effect on moisture content and organoleptic assessment onaroma, flavor, texture, and overall acceptance.Key words: sago, Heat Moisture Treatment, artificial rice, green beans.